On the reliability of majority logic structure in quantum-dot cellular automata. (January 2016) - Sen, Bibhash; Sahu, Yashraj; Mukherjee, Rijoy; Nath, Rajdeep Kumar; Sikdar, Biplab K.
Abstract: Quantum-dot cellular automata (QCA) is projected to be a promising nanotechnology due to its extremely small feature size and ultra low power consumption. However, acceptance of a QCA design is limited due to its high defect rate. Efficient fault tolerant schemes are, therefore, needed for reliable design. This work targets design of a new fault tolerant scheme around QCA logic primitives which encapsulates two different orientations of QCA cell. A 2×2 array of four rotated ('+') cells, called complementary tile (CT), is introduced to maximize the throughput. It ensures 100% fault tolerance under single cell missing defect. Two reliable majority voters (RMV), based on the CT, are designed which outperforms the existing majority logic in QCA. The functional characterization and polarization of RMV under different cell deposition (missing/additional) defects are covered. The significance of the clocking in fault tolerance is also investigated with RMV with multi clock zone. The error probability model for the proposed RMV, under cell deposition (missing/additional) defect, is developed to ensure better understanding of reliability in QCA. Abstract : Highlights: A fault tolerant architecture design based on complementary tile in QCA Nanotechnology. The proposed model ensures high fault tolerance under single missing cell defect providing no other deviation from the ideal architecture than the fact of the missing cell. A reliability estimation model for QCA is proposed in this paper. Fault tolerance of majority is extended to circuit-level.